2013
DOI: 10.1021/ci300399w
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Docking: Improving the Reliability of Docking in a Virtual Screening Context

Abstract: Structure-based virtual screening relies on scoring the predicted binding modes of compounds docked into the target. Because the accuracy of this scoring relies on the accuracy of the docking, methods that increase docking accuracy are valuable. Here, we present a relatively straightforward method for improving the probability of identifying accurately docked poses. The method is similar in concept to consensus scoring schemes, which have been shown to increase ranking power and thus hit rates, but combines in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
195
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(200 citation statements)
references
References 28 publications
5
195
0
Order By: Relevance
“…A very recent approach concerns the introduction of a ligand-based component within the docking protocol that consists in exploiting the ligand information relative to crystallographic ligand-protein complexes for guiding pose selection and ranking, in a sort of combined ligand/receptor-based approach 12,[39][40][41] . Surprisingly, only very few studies evaluated the possibility of combining the results of different docking methods (consensus docking) to obtain reliable ligand binding poses and to improve the success rate in VS studies, as recently reported by Houston and Walkinshaw 42 . Inspired by their analysis, we very recently assessed the reliability of a consensus docking (CD) protocol employing ten different docking procedures at the same time to improve the performance of docking from both a qualitative and a quantitative point of view 43 .…”
Section: Introductionmentioning
confidence: 99%
“…A very recent approach concerns the introduction of a ligand-based component within the docking protocol that consists in exploiting the ligand information relative to crystallographic ligand-protein complexes for guiding pose selection and ranking, in a sort of combined ligand/receptor-based approach 12,[39][40][41] . Surprisingly, only very few studies evaluated the possibility of combining the results of different docking methods (consensus docking) to obtain reliable ligand binding poses and to improve the success rate in VS studies, as recently reported by Houston and Walkinshaw 42 . Inspired by their analysis, we very recently assessed the reliability of a consensus docking (CD) protocol employing ten different docking procedures at the same time to improve the performance of docking from both a qualitative and a quantitative point of view 43 .…”
Section: Introductionmentioning
confidence: 99%
“…However, docking programs (including AutoDock Vina) have more success at predicting the experimentally observed binding modes (poses) of compounds within active sites. 91,100 Our results showed a notable uniformity in the binding locations of the DBS/DBA groups of the 33 ligand structures docked, with the DBS/DBA rings clustered into four distinct binding regions (BR 1 to 4) in the active site of TR (see Fig. 1).…”
Section: Docking Resultsmentioning
confidence: 74%
“…Combining the results from two or more scoring functions and forming a consensus has proved to be more beneficial in scoring and ranking compounds. Consensus scoring has superior accuracy, thereby improving the probability of discovering true potential hits (Cheng et al 2009;Houston and Walkinshaw 2013).…”
Section: Docking and Scoringmentioning
confidence: 99%